Oil Palm Empty Fruit Bunch-Seaweed Biocomposite As Potential Soil Erosion Mitigation For Oil Palm Plantation - Ashikin, Nurin Syahindah Syasya Nor (2018)
Past study confirmed that agriculture (e.g., oil palm plantation) is the main culprit to river sedimentation due to massive erosion from land clearing activities. Soil erosion has four different stages comprising of splash, sheet, rill, and gully. Numbers of soil erosion mitigation approaches using agricultural by-product have been studied. However, current approaches are laborious and not innovative thus, limit the potential of by-product to be applied on matured oil palm plantation only. Plus, current approaches were introduced at splash (first stage) and rills (third stage) erosions only. In this study, we examine the potential of oil palm empty fruit bunch (OPEFB) and wild seaweed (invasive species) as a biodegradable composite for soil erosion mitigation at sheet erosion to increase soil infiltration capacity by regulating runoff volume. The recovery of OPEFB as a reinforced natural fiber in composite has a great potential in absorbing raindrop impact due to its natural hydrophilic characteristic. Besides, such green composite can be developed at lower cost by blending with abundance wild seaweed as a matrix. This research provides an alternative thought of circular economy which emphasizes on agriculture by-product recovery and regeneration to restore a degraded soil system. Therefore, the main objective of this study is to determine the efficiency of the biocomposite in regulating runoff volume and maintaining its water quality. For this reason, investigation of runoff volume, turbidity, and total suspended solid (TSS) on different rates (0 g/ft2 (T1), 250 g/ft2 (T2), 350 g/ft2 (T3), and 500 g/ft2 (T4)) of the composite were observed. In addition, the water absorption and thickness swelling tests of the studied composite was performed according to ASTM D 1037-99. Water absorption and thickness swelling percentages of OPEFB-SW were recorded to be 117.22 ± 7.14% and 10.52 ± 1.73% respectively, showing the capability of this composite to absorb high amount of water while maintaining its physical structure until day 4 of the experiment. Overall, our studied composite demonstrating its capability to absorb rainfall impacts hence stabilize soil structure by reducing soil detachment. In average, it is evidenced that runoff volume, turbidity, and TSS were significantly reduced until 39.1 ± 10.07%, 89.42 ± 5.17%, and 98.88 ± 0.27%, respectively with compared to control plot. Nevertheless, it is suggested that 350 g/ft2 (T3) is the best rate in providing sufficient soil cover. These results served as a baseline data for future soil erosion control in sandy soil texture in oil palm plantation.